Experimental construction of vertical gardens and its relation with thermohygrometric comfort in closed environments - Cabrera Vallejo, Mario (2016)
The aim of the research is to improve the thermo-hygrometric comfort indoors, through the implementation of two prototypes of vertical gardens, one consisting of ferns and another by an association of plants, recording environmental conditions was performed with the Questem team p 34, for 5 days for a cabin volume of 15,35m3 and an area of 4 m2 of garden, these are the wet bulb temperature (Tbh ° C), dry bulb temperature (Tbs ° C) , globe temperature (Tg ° C), relative humidity (% RH), the global wet bulb temperature indoor (TGBHi ° C) and air velocity (v m / s) in booths test prototype without prototype vertical garden in natural and forced convection, according to statistical analysis Pearson correlation is concluded that with the implementation of the prototype of vertical garden plant association have changes in temperature and humidity conditions, air temperature, air humidity environments closed with natural and forced convection.